METHOD FOR THE PATHOGENETIC PREVENTION AND TREATMENT OF INTOXICATION BY THE PESTICIDE DECIS WITH LIPOIC ACID - Mukaddaskhon Askarovna Khamrakulova; Roza Tolanovna Kamilova; Askar Usmanovich Sadikov; Usman Askarovich Sadikov (Scholar Express Journals, 2021)
The use of the pesticide insectoacaracide Decis, if the safety rules are not followed, can cause occupational poisoning. According to the results of the presented research on finding antidotes by neutralizing the poison when poisoning with Decis, lipoic acid was used as a pathogenetic prophylaxis and treatment. Lipoic acid, when combined with the pesticide, forms a neutral, non-toxic compound in the form of a Decis + Lipoic acid complex, which leads to the normalisation of disturbed metabolic processes.
Keywords: Pesticide Decis; intoxication; prevention; neutralisation